Educating in an Era of Orwellian Spin: Critical Media Literacy in the Classroom - Orlowski, Paul (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
Canadians live in a world of mega‐spin where public relations corporate lobbyists play an increasingly larger role in news‐making. To resist this trend, I have studied political ideology to understand the relationship between corporate media and systems of social, economic, and political power, and their hegemonic function, and indicate the bias inherent in the media, a contention that assumes the epistemological position that all knowledge is socially constructed. I demonstrate how preservice education students can acquire this understanding by reframing political discourse from different ideological perspectives, and how teachers can integrate critical media literacy into high‐school social studies courses. Key words: social studies, teacher education, ideology critique Les Canadiens vivent dans un monde où lobbyistes et spécialistes des relations publiques d’entreprises jouent un rôle de plus en plus prépondérant dans les nouvelles qui leur sont présentées. Soucieux de résister à cette tendance, l’auteur analyse l’idéologie politique en vue de mettre en lumière la relation entre les médias et les systèmes de pouvoir sociopolitique et économique et leur rôle hégémonique. Il fait en outre ressortir la partialité des médias, une affirmation qui repose sur le principe épistémologique selon lequel le développement de toute connaissance est de nature sociale. L’auteur montre comment des étudiants en sciences de l’éducation peuvent se sensibiliser à cette réalité en resituant le discours politique au sein de diverses perspectives idéologiques et comment les enseignants peuvent intégrer l’initiation aux médias et la promotion de l’esprit critique dans les cours de sciences humaines au secondaire. Mots clés : sciences humaines, formation à l’enseignement, critique des idéologies